PEMANFAATAN INFRASTRUKTUR JALAN UNTUK MENDUKUNG PERTUMBUHAN EKONOMI MASYARAKAT - Hamirul,; Joko Sunaryo, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
The construction of road infrastructure is a necessity for the community, especially in the village as a marketing distribution channel for agricultural products produced by farmers. By using descriptive methods and qualitative approaches. Data collection techniques using interviews with informants as many as 7 people. Research Results The use of road infrastructure to support economic growth in Sungai Beringin Hamlet has been effective, because the community has benefited from the roads that have been built by the Sungai Beringin Hamlet government, but the community is still not satisfied with the services provided by the local government in this case the government Bungo Regency, because the community is still having difficulty passing the roads in the Beringin River sub-district with the status of a road, especially the access road to the Beringin River village is still integrated with the company's road.